A review of the genus Pholcus (Araneae: Pholcidae) from China - Zhang, Feng; Zhu, Ming-Sheng (Zootaxa, 2009)
A total of 55 species of the genus Pholcus occurring in China are reviewed here. Among them, 20 species are new to science: Pholcus dali sp. nov., P. fengcheng sp. nov., P. harveyi sp. nov., P. huberi sp. nov., P. kangding sp. nov., P. kunming sp. nov., P. mianshanensis sp. nov., P. paralinzhou sp. nov., P. parayichengicus sp. nov., P. phoenixus sp. nov., P. saaristoi sp. nov., P. shangrila sp. nov., P. songi sp. nov., P. songxian sp. nov., P. sublingulatus sp. nov., P. subwuyiensis sp. nov., P. yangi sp. nov., P. yugong sp. nov., P. zhangae sp. nov., P. zhuolu sp. nov. One new combination is formed: Pholcus elongatus (Yin & Wang, 1981) is transferred from Spermophora. One species, P. opilionoides, has not yet been found in China.